Cryptococcus gattii and Cryptococcus albidus in captive domestic Pigeon (Columba livia) - Werther, Karin [UNESP]; Sousa, Eliane de [UNESP]; Alves Júnior, José R. F. [UNESP]; Ardisson, Francisca A. [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (My University, 2011)
Cryptococcosis in animals is an important fungal disease caused by the encapsulated yeast Cryptococcus neoformans. This report describes the occurrence of Cryptococcus gattii and Cryptococcus albidus in domestic pigeon (Columba livia), living together with other birds in a breeding center. The animal presented a pinkish, vascularized mass with gelatinous aspect localized subcutaneously under the right lower eyelid, with approximately 2cm in diameter. At microbiological exam it was isolated Cryptococcus gatti from the eyelid mass, lungs and liver, C. albidus from the trachea and both Cryptococcus species from muscle and kidney.
Keywords: Bird diseases; Cryptococcus albidus; Cryptococcus gatti; Public health